2010
DOI: 10.1111/j.1559-1816.2010.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Partisan Prejudice: Selective Distortion and Weighting of Evaluative Categories in College Admissions Applications

Abstract: Two methods by which people make prejudicial yet justifiable judgments were assessed in a simulated college admissions paradigm in which participants evaluated 2 applications. In the preference condition, the stronger applicant was described as a member of a different political party than the participant. In the control condition, no political party was indicated. Supporting a political partisan prejudice effect, among strong partisans, the stronger applicant was favored in the control condition, but the weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…The potential for political bias is likely greatly reduced when researchers seek to explain the motivations, foibles, and strengths of liberals as well as conservatives. Several programs of research have found evidence of strengths and weaknesses among both liberals and conservatives, including moral foundations theory (e.g., Haidt 2012), the ideologically objectionable premise model (Crawford 2012;Crawford & Xhambazi 2015), and the ideological conflict hypothesis (e.g., Brandt et al 2014;Munro et al 2010). This evidence disconfirms the hypothesis that conservatives really do warrant relentless scientific condemnation.…”
Section: Risk Point 3: Negative Attitudes Regardingmentioning
confidence: 99%
“…The potential for political bias is likely greatly reduced when researchers seek to explain the motivations, foibles, and strengths of liberals as well as conservatives. Several programs of research have found evidence of strengths and weaknesses among both liberals and conservatives, including moral foundations theory (e.g., Haidt 2012), the ideologically objectionable premise model (Crawford 2012;Crawford & Xhambazi 2015), and the ideological conflict hypothesis (e.g., Brandt et al 2014;Munro et al 2010). This evidence disconfirms the hypothesis that conservatives really do warrant relentless scientific condemnation.…”
Section: Risk Point 3: Negative Attitudes Regardingmentioning
confidence: 99%
“…higher grades). 31 Partisans also judge hypocrisy by opposing party politicians more harshly. 32 Party attachments even lead partisans to support policies they normally would reject, as evident from experiments manipulating party endorsement of welfare policies.…”
Section: Politics and Cognitive Biasmentioning
confidence: 99%
“…These divisions go far beyond simple disagreements over which policies are best. Americans actively avoid communicating with and openly discriminate against people with different political beliefs (Goldman & Mutz, 2011;Munro, Lasane, & Leary, 2010). This distance between political opponents can be observed in the media in the form of a separation of liberal and conservative Twitter users in the sharing of political tweets and increasing segregation of political blogs (Adamic & Glance, 2005;Conover et al, 2011).…”
Section: Tweeting Morals In the 2016 Electionmentioning
confidence: 99%